Damage evaluation of a simplified hull girder subjected to underwater explosion load: A semi-analytical model. (January 2016) - Wang, Hao; Cheng, Yuan Sheng; Liu, Jun; Gan, Lin
Abstract: A new analytical model to predict the damage of a simplified hull girder (SHG) subjected to underwater explosion (UNDEX) shock wave load and following bubble pulsation load is presented. In the shock wave phase, the rigid-plastic material model and triangular pressure distribution assumption are adopted to build the governing equations. Based on this model, a new damage indicator of a SHG is derived and discussed. In the bubble pulsation phase, damage types and severity are evaluated based on the Vernon bubble model and the modified hydro-plastic series equations. Analytical results are compared with experimental data and numerical simulations. It is shown that the proposed model is able to capture the essential response features and damage types of a SHG both in shock wave phase and in bubble pulsation phase. Highlights: A novel semi-analytical model to predict the underwater explosion damage of a simplified hull girder (SHG) is presented. The semi-analytical results are corroborated by numerical analysis. The effects of a SHG assumption are discussed. A simple damage indicator χ is derived. The χ being less than 0.4598 gives a sufficient condition that a SHG keeps rigid.